Strategi Perencanaan Pembelajaran PAI Berbasis IT untuk Meningkatkan Minat Belajar Siswa Madrasah Tsanawiyah Al-Hikmah Janti Jogoroto - Umul Khoirun Nisa; Mohammad Saat Ibnu Waqfin (ISLAMIKA, 2023)
The development of this learning is based on the existence of developments in various knowledge which in this day and age has raced on information and communication technology which has an important role in the world of education. Because basically the world of education today has been entered by the fifth revolution. In the learning process, there are still many teachers who use the lecture learning method which causes students to feel bored in learning so that it resulting in students not being interested in learning, this requires teachers to be creative in using IT learning media to attract students' interest. This study aims to 1) describe the IT-based Islamic Religious Education learning planning strategy at MTs Al-Hikmah Janti Jogoroto. 2) to find out the obstacles and strengths in the learning process by using IT at mts al-hikmah Janti. (2) The method used in this research is descriptive qualitative research. Data collection techniques in this study used questionnaires, observation, interviews, and documentation. Data analysis is carried out using the method of collecting and reviewing existing data, then carrying out data reduction, presenting data, and presenting data in the form of conclusions. The final stage of data analysis is the validity of the data using credibility (trust) techniques. (3) The results of this study indicate that IT media has been applied in the learning process. Students also look very enthusiastic when given material through the LCD (projector). besides that with the existence of IT-based media students become more interested in learning which also makes it easier for students in the learning process. Therefore it can be concluded that the existence of IT-based media can make students not bored during the learning process and also make it easier for students in the learning process.